Sri Lanka Development Update, June 2018 : More and Better Jobs for an Upper Middle-Income Country - World Bank (World Bank, Washington, DC, 2018)
Recent policy measures have contributed to macroeconomic stability. However, with significant risks stemming from both domestic and external fronts, the balance of risks is tilted towards downside. To sustain growth, create more and better jobs and reduce poverty Sri Lanka needs to implement and sustain structural reforms to improve competitiveness. This Special Focus section looks at the state of jobs and the job creation challenge in Sri Lanka compared to the South Asian Region and zooms in on labor force participation of women and in Sri Lanka’s post-conflict areas.